MODIFIED ALVARADO SCORING SYSTEM. HOW MUCH HELPFUL? - Rassam, Raid . E (AL-Kindy College Medical Journal, 2011)
Background:-The Modified Alvarado ScoringSystem (MASS) has been reported to be a cheapand quick diagnostic tool in patients with acuteappendicitis. However, differences in diagnosticaccuracy have been observed if the scores wereapplied to various populations and clinical settings.Objectives:- The purpose of this study was toevaluate the diagnostic value of Modified AlvaradoScoring System in patients with acute appendicitisin our setting.Methods:-one hundre twenty eight patients, wereincluded in this study, admitted to Al-Kindyteaching hospital from June 2009 to June 2010.Patients’ age ranged from 8 to 56 years (21±10)they were divided into three groups; paediatrics,child bearing age females & adult males,. MASSwas calculated for each patient included as thediagnosis & treatment were done on the bases ofsurgeon's clinical decision,confirmation was doneby histopathological examination. Finally statisticsdone included negative appendectomy rate,sensitivity, specificity, positive predictivevalue,negative predictive value & accuracy.Results: - Our negative appendectomy rate was19.5% (22.22% for paediatrics 40.9% for females4.2% for males). MASS showed sensitivity of61%(92.8% for paediatrics 38% for females & 58%for males), specificity 80% (75% for paediatrics88% for females & 50% for males), positivepredictive value 92%(92.8% for paediatrics 83%for females 50% for males), negative predictivevalue 33% (75%for paediatrics 50% for females5% for males) & accuracy 65% (88.9% forpaediatrics 59% for females 58% for males).Conclusion:- MASS was of limited help to juniordoctors in our setting,clinical assessment &experience are still the gold standard for acuteappendicitis.